Biological Roles of Aberrantly Expressed Glycosphingolipids and Related Enzymes in Human Cancer Development and Progression - Zhuo, Dinghao; Li, Xiang; Guan, Feng (Frontiers in Physiology, 2018)
Glycosphingolipids (GSLs), which consist of a hydrophobic ceramide backbone and a hydrophilic carbohydrate residue, are an important type of glycolipid expressed in surface membranes of all animal cells. GSLs play essential roles in maintenance of plasma membrane stability, in regulation of numerous cellular processes (including adhesion, proliferation, apoptosis, and recognition), and in modulation of signal transduction pathways. GSLs have traditionally been classified as ganglio-series, lacto-series, or globo-series on the basis of their diverse types of oligosaccharide chains. Structures and functions of specific GSLs are also determined by their oligosaccharide chains. Different cells and tissues show differential expression of GSLs, and changes in structures of GSL glycan moieties occur during development of numerous types of human cancer. Association of GSLs and/or related enzymes with initiation and progression of cancer has been documented in hundreds of studies, and many such GSLs are useful markers or targets for cancer diagnosis or therapy. In this review, we summarize (i) recent studies on aberrant expression and distribution of GSLs in common human cancers (breast, lung, colorectal, melanoma, prostate, ovarian, leukemia, renal, bladder, gastric); (ii) biological functions of specific